(3COH GdChUjGAs - (3GdLeGdj , YdGA GdOjf Ydj Hf CMeO Hf eMeO GdQhej GdMfaj,J (B932 (3g` s ((3eSYhO GdfGHdSi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdUdGI hGdSdGe Ydi CaVd GdCfHjGA hHYO agPG cJGH COH GdChUjGA GdPi LeYJg ai HdO Gddg GdMQGe s
(3BNQgG (B:s
(3HYO ehJg HEjeGfg Edjg dCfg cGdJhcjd , hjQi ai GdeSCdI YOe LhGR JUQag CjVkG dcf GdUMjM gh GdUMI GdMeO ddg hMOg hGdUdGI hGdSdGe Ydi ef dGfHi HYOg JeJ s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B258 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B25 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B742s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B45s
Keywords: (3GdCOHs